Phenotypic plasticity and nonstructural carbohydrates in annual growth rings of the australian red cedar clones in contrasting enviroments - Rosado, Lucas Rodrigues (2019)
Nonstructural carbohydrate (NSC) reserves are associated with plant growth and their resilience mechanisms when exposed to environmental stresses, especially to the soil water deficit.Thus, the objective of this study was to evaluate the influence of the contents of NSC in the trunk on the survival, growth, and phenotypic plasticity regarding the increase rate of the sectional area (ISA), as well as to support the selection of more resilient genotypes when subjected to more severe or prolonged drought periods. The evaluated NSC (starch, sucrose, reducing sugars, total soluble sugars, and total NSC) and the ISA were estimated in the annual trunk growth rings in wood discs removed at 1.3 m from the ground level. A total of ten clones (fd, fe, hf, md, mi, xd, xe, xf, xg, xi) from Toonaciliata M. Roem. var. australis (Australian cedar), with seven years of age and obtained from two sites with contrasting water stress conditions, were studied. Both sites are in the state of Minas Gerais, in the municipalities of Campo Belo (CBL) and Cana Brava (CNB), presenting lower and higher levels of water stress, respectively. The NSC contents were estimated using multivariate models generated by the near-infrared spectroscopy (NIR) technique. Partial least squares regression was used to associate the amount of NSC obtained by conventional laboratory analysis with the NIR spectral signatures. These models were validated in an external data set, which demonstrated the satisfactory application of the adjusted models to estimate the NSC contents in the growth rings of the ten clones. The width of the growth ring of each clone was measured and transformed into ISA. The average effects of the clones and their phenotypic plasticity were estimated using random regression models, while the correlations between the model parameters were analyzed by Pearson correlation coefficients. The high and significant correlations of 0.96 and 0.97 were obtained for the mean total NSC content and the phenotypic plasticity of ISA in CBL and CNB, respectively. When correlated with the sucrose accumulation rate, the phenotypic plasticity for ISA was high and significant only in CBL (r=0.82), and when correlated with the total NSC accumulation rate, it was positive and significant (r=0.72) for CBL and negative and significant (r=-0.99) for CNB. Clone survival is inversely correlated with the mean values of reducing sugars (r=-0.90) and the accumulation rates of starch (r=-0.91), reducing sugars (r=-0.66), and total NSC (r=-0.99), suggesting that the depletion of these NSC was necessary to maintain life. The highest performance and phenotypic plasticity of clone “xd”, verified over the study period, showed that, among all studied clones, this one was the most resilient in both stress conditions.